Meristic and morphological characterization of the freshwater prawn, Macrobrachium macrobrachion (Herklots, 1851) from the Mono River – Coastal Lagoon system, Southern Benin (West Africa): Implications for species conservation - ADITE, ALPHONSE; ABOU, YOUSSOUF; SOSSOUKPE, EDMOND; GBAGUIDI, M. H. A. Gildas; FIOGBE, EMILE DIDIER (My University, 2013)
The freshwater prawn, Macrobrachium macrobrachion is one of the shrimp’s species that contribute to the fisheries in the Mono River – Coastal Lagoon water system of the Southern Benin, where major causes of environmental degradation that affect species integrity and survival, are hydro electrical dam, bridges, mangrove destruction, water hyacinth invasion, dumping of domestic wastes from a public market, use of detrimental fishing gears and overfishing. A total of 780 specimens of M. macrobrachion were sampled from two locations to investigate the morphological and taxonomic characterization of the species and to detect whether the population is morphologically and taxonomically separable in order to ascertain possible genetic diversity. The population exhibited significant (P≤0.01) morphological relationships with positive slopes varying between 0.28 and 2.80 and coefficients of correlation “r” between 0.70 and 0.96. The positive slopes “b”<3 (2.80 for Heve location; 2.71 for Onkuiwe location) from the total length - body weight relationships suggest that M. macrobrachion exhibited an allometric growth in the Mono River – Coastal Lagoon system. The results indicated that the morphometric features across the two sub-populations of M. macrobrachion were not significantly different (0.00001 ≤ F1,778 ≤ 0.205, P ≥0.05). Computed body proportions revealed that the prawn was twice as long as its cepholothorax and twice as long as its abdomen. Also, the cephalothorax was as long as the dorsal rostrum and twice as long as its height. The total length was 4.9-8.69 times the uropod length and 5.17-9.45 times the telson length, and the cephalothorax length was 6-8.83 times the eye diameter. Also, the meristic counts from the two sub-populations of M. macrobrachion were not significantly different (0.000001 ≤ F1,778 ≤ 0.000003, P ≥0.05). M. macrobrachion had 12-15 rostral spines at the dorsal side of the rostrum and 3-5 rostral spines at the ventral side. As a results the morphometric measurements and the meristic traits of M. macrobrachion from the two (2) locations did not differ significantly (P≥0.05), indicating that the population of M. macrobrachion in the Mono River – Coastal Lagoon system of Benin is morphologically and taxonomically inseparable and, consequently, may not be genetically diversified. Hence, search in genetic diversification requires molecular characterization to detect eventual variation among the population. Also, for species conservation and habitat protection purpose, the output generated from this study will form documentation for this prawn and serve as reference for species follow-up pending any further changes in the ecosystem.
Keywords: Degradation; genetic diversification; Macrobrachium macrobrachion; morphological; characterization; Mono River; species conservation; sympatric speciation.